Effect of 5-Fluorouracil on liver regeneration and metabolism after partial hepatectomy in rat - Hakan M. KÖKSAL; Levent ERDEM; Sadık YILDIRIM; Turgut İPEK and Işıl PAKİŞ (Turkish Journal of Gastroenterology, 2019)
-